Accompanying Pulmonary Arteriovenous Malformation in Patient with Hydatidiform Mole: A Case Report - Bak, So Hyeon; Yoon, Hye-Kyung; Jeon, Young Wook; Ko, Jung Hwa; Lee, Bong-Ki (Journal of the Korean Society of Radiology, 2017)
The most common site of metastasis in gestational trophoblastic disease (GTD) is the lung. To the best of our knowledge, arteriovenous malformations (AVMs) associated with pulmonary metastatic lesions are extremely rare in patients with GTD. Here, we report a case of a nineteen-year-old woman who presented with pulmonary AVMs which developed in the areas of pulmonary metastases, complicated by recent hemorrhage.